An experimental water line list at 1950 K in the 6250–6670 cm−1 region. (January 2018) - Rutkowski, Lucile; Foltynowicz, Aleksandra; Schmidt, Florian M.; Johansson, Alexandra C.; Khodabakhsh, Amir; Kyuberis, Aleksandra A.; Zobov, Nikolai F.; Polyansky, Oleg L.; Yurchenko, Sergei N.; Tennyson, Jonathan
Highlights: New 1950 K absorption spectrum of water recorded in methane/air flame. 2417 lines identified in the 6250–6670 cm − 1 region. 2030 of these lines are assigned using a new variational line list yielding 127 new water energy levels. Graphical abstract: Abstract: An absorption spectrum of H2 16 O at 1950 K is recorded in a premixed methane/air flat flame using a cavity-enhanced optical frequency comb-based Fourier transform spectrometer. 2417 absorption lines are identified in the 6250–6670 cm − 1 region with an accuracy of about 0.01 cm − 1 . Absolute line intensities are retrieved using temperature and concentration values obtained by tunable diode laser absorption spectroscopy. Line assignments are made using a combination of empirically known energy levels and predictions from the new POKAZATEL variational line list. 2030 of the observed lines are assigned to 2937 transitions, once blends are taken into account. 126 new energy levels of H2 16 O are identified. The assigned transitions belong to 136 bands and span rotational states up to J = 27 .